AD synapses contain abundant Aβ monomer and multiple soluble oligomers, including a 56 kDa assembly - Sokolow, Sophie (2011)
Much evidence indicates that soluble amyloid beta (Aβ) oligomers are key mediators of early cognitive loss, but the localization and key peptide species remain unclear. We have used flow cytometry analysis to demonstrate that surviving Alzheimer's disease (AD) synapses accumulate both Aβ and p-tau. The present experiments use peptide-specific xMAP assays and Western blotting to identify the Aβ peptide species in synaptosome-enriched samples from normal human subjects, neurologic controls, and AD cases. Aβ40 peptide levels did not vary, but both Aβ42 and Aβ oligomers were increased in soluble AD extracts, with oligomer levels 20-fold higher in aqueous compared to detergent extracts. In Western blots, a ladder of SDS-stable oligomers was observed in AD cases, varying in size from monomer, the major peptide observed, to larger assemblies up to about 200 kD and larger. Multiple oligomers, including monomer, small oligomers, a 56 kD assembly, and APP were correlated with the Aβ level measured in flow cytomety-purified synaptosomes. These results suggest that multiple APP processing pathways are active in AD synapses and multiple soluble oligomeric assemblies may contribute to synaptic dysfunction.